Analysis of the Effect of Adding Jatropha Seed Shell on the Physical and Thermal Properties of Recycled Polypropylene Composites - Siti Masluhah, Via; Br Sembiring, Enjelika; Nasution, Chinta Radjeli Putri; Dwi Suyatmo, Reviana Inda; Santoso, Teguh Budi (Journal of Chemical Process Engineering, 2024)
The increasing volume of plastic waste, particularly polypropylene (PP), poses a significant environmental challenge. Recycling is a crucial solution but often leads to degradation of PP's mechanical and thermal properties of PP. This study aims to enhance recycled PP quality by adding a natural filler in the form of Jatropha Seed Shell (JSS). JSS is a potential filler due to its good mechanical and thermal properties, low density, and recyclability. The research was conducted in two parts: first, without alkalization treatment, using recycled PP with varying JSS additions at 0%, 5%, 10%, 15%, and 20%. The Melt Flow Rate (MFR) test without JSS showed an average value of 20.620 g/10 minutes, decreasing to 15.380 g/10 minutes at 20% JSS. JSS addition also increased crystallinity from 30.92% to 36.14% and melting temperature from 163.9°C to 166.4°C with 20% JSS. The second part, with alkalization treatment using a 20% NaOH solution, aimed to improve JSS compatibility with the PP matrix.  The results showed that alkalization treatment improved the distribution of the filler within the matrix, leading to enhanced mechanical and thermal properties. The MFR value decreased more significantly in this treatment compared to without alkalization, with the lowest value at 14.55 g/10 minutes in the composite with 20% JSS. The degree of crystallinity increased to 33.9% with 15% JSS addition, while the melting temperature remained stable.